1990
DOI: 10.1002/cne.903020209
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic, GABAergic, and hippocamposeptal innervation of gabaergic “somatospiny” neurons in the rat lateral septal area

Abstract: This study deals with the neurochemical characterization of the rat lateral septal area (LSA) somatospiny neurons and their innervation by hippocamposeptal, catecholaminergic, and GABAergic fibers. Electron microscopic single and double immunostaining methods were used to label catecholaminergic fibers and GABAergic cells and boutons. Axon terminals originating in the hippocampus were labeled by acute anterograde axon degeneration induced by fimbria-fornix transection 36 hours before sacrifice. Three types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…DA is involved in the modulation of the activity at all levels within the septal circuitry: in the regulation of the hippocamposeptal pathway by the influence of glutamatergic hippocampal neurons, in the septohippocampal route over cholinergic cells in the medial septum/diagonal band nucleus (Robinson et al, 1979;Costa et al, 1983), and finally, influencing GABAergic neurons of the lateral septum (Jakab and Leranth, 1990). Robinson and coworkers (1979) demonstrated a role of the mesolimbic DA system in the regulation of the turnover rate of acetylcholine in the hippocampus.…”
Section: Functional Actions Of Ca In the Septummentioning
confidence: 98%
See 2 more Smart Citations
“…DA is involved in the modulation of the activity at all levels within the septal circuitry: in the regulation of the hippocamposeptal pathway by the influence of glutamatergic hippocampal neurons, in the septohippocampal route over cholinergic cells in the medial septum/diagonal band nucleus (Robinson et al, 1979;Costa et al, 1983), and finally, influencing GABAergic neurons of the lateral septum (Jakab and Leranth, 1990). Robinson and coworkers (1979) demonstrated a role of the mesolimbic DA system in the regulation of the turnover rate of acetylcholine in the hippocampus.…”
Section: Functional Actions Of Ca In the Septummentioning
confidence: 98%
“…In addition, DA has a concentrationdependent modulatory effect on other neurotransmitters, such as Glu and ␥-aminobutyric acid (GABA) (Chiodo and Berger, 1986). Jakab and Leranth (1990) suggested that high levels of DA release in the septum can result in depression in the activity of lateral septal neurons, whereas basal levels of DA release can maintain their sensitivity to both excitatory and inhibitory inputs.…”
Section: Functional Actions Of Ca In the Septummentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there is an extensive intrinsic arborization of the axons of GABAergic projection neurons inside the LS organized in subregional circuits (Jakab and Leranth, 1995). These fibers and potential extrinsic, GABAergic sources (Jakab and Leranth, 1990) probably cause the heavy homogeneous VGAT-ir of the LS which was -similar to VGLUT1 and VGLUT2 -only rarely co-expressed with VGLUT3-ir.…”
Section: Coincidence Of Vglut3-ir With Markers That Define Major Neurmentioning
confidence: 99%
“…Possibly relevant to this, neuroanatomical studies have shown that the ventral lateral septum generates a strong projection to the rostral bed nucleus (Staiger and Nurnberger 1991) including zones targeted by the medial amygdala (Canteras et al 1995), whereas physiological work points to a close relationship between the ventral lateral septum and the bed nucleus (Mathieson et al 1989). The lateral septum, including its ventral aspect, contains high concentrations of GABAergic neurons (Kohler and Chan-Palay 1983;Panula et al 1984;Jakab and Leranth 1990;and others), which would be expected to suppress responses by bed nucleus neurons to activity in the presumably glutamatergic medial amygdala (McDonald and Augustine 1993;Shindou et al 1993;Pitkanen and Amaral 1994). According to this hypothesis, the weaker medial projection to the septum can serve, on some occasions, to cancel the effects of the stronger medial amygdalar projection to the bed nucleus (Canteras et al 1995; see schematic in Fig.…”
Section: Explorationmentioning
confidence: 99%